Effect of burnishing on Inconel 718 workpiece surface heated by infrared radiation - Casarin, Samuel José [UNESP] (2021)
Roller burnishing process is a post-machining surface finishing technique that has an advantage over other finishing processes, such as shot blasting or abrasive-tooling processes, because of its simplicity and excellent results (both improved surface finish and improving the mechanical properties of the material). Roller burnishing allows you to eliminate the part grinding step. Nickel super alloys, in turn, including the Inconel 718 have wide application in the aerospace industry due to their high fatigue strength and their ability to work at elevated temperatures. The Inconel 718 shows a predominantly austenitic matrix (γ phase), which under the burnishing process trends to produce an increase in hardness and residual stress. This paper is the result of research on the influence of the conventional roller rolling process at room temperature and at 310°C on a turned part of Inconel 718. Results of surface roughness, roundness deviation, microhardness, residual stress, and deformation of the material under a load of 850 N were analyzed. The obtained results prove the improvement of the material properties after the roller burnishing process: lower values of surface roughness, higher roundness deviation in conventional burnishing, higher surface hardness and higher compressive residual stress in hot burnished specimen.